Design and Application of the Production Information System at PT Datang DSSP Power Indonesia - Wang Zhiliang (Al-Makki Publisher, 2025)
This study investigates the design, implementation, and evaluation of a real-time Production Information System (PIS) developed for PT Datang DSSP Power Indonesia, a joint-venture corporation operating three coal-fired power plants. Increasing operational complexity in thermal power generation demands integrated monitoring solutions that enhance production efficiency, strengthen safety management, and improve decision-making processes. This research aims to develop and assess a PIS capable of delivering real-time production data while supporting centralized supervision through a set of interconnected technological modules. The study employs a system design approach based on operational requirements, phased technological implementation, and functional performance evaluation. The proposed PIS integrates four core components: a site-wide Closed-Circuit Television (CCTV) system, real-time production data acquisition and upload, a video conferencing platform, and secure broadband connectivity enabling reliable data transmission to the corporate headquarters. The implementation of the PIS demonstrates substantial improvements in production efficiency, safety monitoring, and resource allocation. The system enhances cross-site visibility, supports faster situational assessment, and accelerates strategic decision-making within the organization. Overall, the findings provide a valuable reference for developing integrated monitoring and information systems in the thermal power generation industry and highlight the broader applicability of such systems to other technology-driven energy sectors.